The Compliance Effects of the Automatic Exchange of Information: Evidence from the Swiss Tax Amnesty - Enea Baselgia (CESifo GmbH, 2025)
This paper studies the effects of the 2017 multilateral automatic exchange of information (AEoI) on tax compliance in Switzerland. Using detailed administrative tax data and difference-in-differences designs, I find significant positive compliance effects. The AEoI prompted 107k taxpayers (2% of all) to participate in the amnesty, disclosing CHF 42.3 billion—over 6% of GDP. At the micro level, once evaders participate in the amnesty, their reported wealth increases by approximately 50% on average, with compliance effects persisting in the medium run. Furthermore, I document that tax evasion in Switzerland is widespread and significantly more evenly distributed than in other countries.
Keywords: D31; F38; F42; H24; H26; K34; K42; 330; tax evasion; AEoI; compliance; enforcement; CRS; tax amnesty; inequality